Pengaruh Modal, Tenaga Kerja, dan Bahan Baku terhadap Hasil Produksi Industri Pengolahan Kayu di Kelurahan Alalak Selatan dan Kelurahan Alalak Tengah Kecamatan Banjarmasin Utara - Ahmad Hafie; Ahmad Yunani (PPJP Universitas Lambung Mangkurat, 2021)
The purposes of this research are (1) to know how the finances, worker, and raw material influence the wood processing industry; (2) to know which most dominant factor influences the wood processing industry in Banjarmasin City. This Research uses quantitative method with primer data obtains from the result of interview and questionnaire. The data are calculated using double linier analysis which will be use test f (simultaneous) and test t (partial).The result of the Research shows that the factors of the finances worker, and raw material influences significantly and positively to the wood processing industry simultaneously and partially. Workers becomes the most dominant factor influencing the output of the wood processing industry.The suggestions given based on the results of the analysis and discussion in this study (1) The owner of a wood processing industry business should be able to pay attention to several factors that can affect production results in order to increase production output; (2) Increase the demand for wood by means of good promotion and marketing by utilizing increasingly developing technology.